TOXIC EFFECT OF PHARMACEUTICALS WITH REFERENCE TO OXYTETRACYCLINE - SHARMA, MADHU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Manufacturing and release of pharmaceuticals are increasing in different countries of the world especially in developing countries. The discharge from wastewater plant contains a wide range of classes of pharmaceuticals. Rapidly growing economy, aquaculture, and livestock industry has led to increased incidences of diseases and has increased the release of pharmaceuticals into natural environment which is affecting the biodiversity of hotspots adversely. This review mainly focuses on antibiotic oxytetracycline, its use, structure, occurrence in aquatic environments and other environmental compartments, lastly an overview of toxicity to fish is provided. The threats posed by these pharmaceuticals are evident from the studies showing their toxic effect on different aquatic organisms.